EFEKTIVITAS PENDEKATAN MATEMATIKA RELISTIK UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Reni Puspita Ningsih (Universitas Muhammadiyah Lampung, 2021)
This study aims to determine the effectiveness of a realistic mathematical approach to improve learning activities and students' mathematical representation abilities. The population in this study were all seventh grade students in one of the public junior high schools in Bandar Lampung in the 2011/2012 academic year which were divided into 9 classes with class divisions consisting of 3 classes with high early ability, 3 classes with moderate early ability, and 3 classes with moderate ability. low start. The students' initial abilities are taken from students' national exam scores at the elementary school level. The class taken in this study is a class that has a high initial ability. Sampling was taken using the Purposive Random Sampling Technique. The samples taken in this study were 2 classes of high early ability from 3 classes of high early ability and obtained classes VII C and VII D which consisted of 65 students with 34 male students and 31 female students. Data was collected using observation techniques based on observation sheets and test techniques using test instruments that were arranged based on the indicators to be achieved. As for what can be concluded from this research is the Realistic Mathematics Approach is effectively applied to the mathematics learning of students with high initial ability to improve learning activities and mathematical representation abilities.